2016
DOI: 10.5312/wjo.v7.i5.308
|View full text |Cite
|
Sign up to set email alerts
|

From Cape Town to Cambridge: Orthopaedic trauma in contrasting environments

Abstract: AIM:To compare the trauma experience gained by a trainee at a United Kingdom major trauma centre and a secondary level hospital in South Africa. METHODS:A profile of inpatient trauma cases during a five-week period in Addenbrooke's Hospital, Cambridge and Somerset Hospital, Cape Town was created. This was achieved by recording various parameters for each patient admitted including age, gender, injury, mechanism of injury and postal/area code. This, together with details of the departments themselves, allows a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…Similar to findings from studies conducted elsewhere, 6,7,22,23 our study showed that the majority of patients admitted were males,with a male-to-female ratio of 7:3. The sex difference may be due to the fact that males tend to exhibit more risky behaviour 15,16 and are perhaps more involved in outdoor activities than females.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to findings from studies conducted elsewhere, 6,7,22,23 our study showed that the majority of patients admitted were males,with a male-to-female ratio of 7:3. The sex difference may be due to the fact that males tend to exhibit more risky behaviour 15,16 and are perhaps more involved in outdoor activities than females.…”
Section: Discussionsupporting
confidence: 90%